CONTRIBUTION OF NON MIGAS CREATIVE INDUSTRY, WEST JAVA TOWARDS INDONESIAN NATIONAL EXPORT (International Journal of Psychosocial Rehabilitation, 2020)
Creative Industry is a business unit managed by the community with a high degree of flexibility, both in terms of financing, management, resources, technology and markets Therefore almost all levels of society are no strangers to this institution. The simplicity of this business unit in terms of both its requirements and implementation in the community, pushed the direction of research to test how much this institutional contribution to the value of West Java and national exports for the past 5 years. By using secondary data sources and verification methods of verification with trend analysis and comparative models, it was found that the contribution of this sector to the average of West Java exports for the last five years was 5.44 billion USD from West Java's contribution to the national non-oil sector's national exports by an average 25.25 billion USD, this value is quite large and significant for West Java exports. Based on the study results, it can be concluded that the contribution of MSMEs from the Creative Industry business unit sector to West Java and national non-oil and gas exports is very significant and large. This sector needs to get the attention of policy makers in the country, by pushing traditional Micro, Small and Medium Enterprises (UMKM) to the creative industry with appropriate regulations.